Prevention of Coronavirus Disease 2019 Among Older Adults Receiving Pneumococcal Conjugate Vaccine Suggests Interactions Between Streptococcus pneumoniae and Severe Acute Respiratory Syndrome Coronavirus 2 in the Respiratory Tract. (9th March 2021) - Lewnard, Joseph A; Bruxvoort, Katia J; Fischer, Heidi; Hong, Vennis X; Grant, Lindsay R; Jódar, Luis; Gessner, Bradford D; Tartof, Sara Y
Abstract: Background: While secondary pneumococcal pneumonia occurs less commonly after coronavirus disease 2019 (COVID-19) than after other viral infections, it remains unclear whether other interactions occur between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and Streptococcus pneumoniae . Methods: We probed potential interactions between these pathogens among adults aged ≥65 years by measuring associations of COVID-19 outcomes with pneumococcal vaccination (13-valent conjugate vaccine [PCV13] and 23-valent pneumococcal polysaccharide vaccine [PPSV23]). We estimated adjusted hazard ratios (aHRs) using Cox proportional hazards models with doubly robust inverse-propensity weighting. We assessed effect modification by antibiotic exposure to further test the biologic plausibility of a causal role for pneumococci. Results: Among 531 033 adults, there were 3677 COVID-19 diagnoses, leading to 1075 hospitalizations and 334 fatalities, between 1 March and 22 July 2020. Estimated aHRs for COVID-19 diagnosis, hospitalization, and mortality associated with prior PCV13 receipt were 0.65 (95% confidence interval [CI], .59–.72), 0.68 (95% CI, .57–.83), and 0.68 (95% CI, .49–.95), respectively. Prior PPSV23 receipt was not associated with protection against the 3 outcomes. COVID-19 diagnosis was not associated with prior PCV13 within 90 days following antibiotic receipt, whereas aHR estimates were 0.65 (95% CI, .50–.84) and 0.62 (95% CI, .56–.70) during the risk periods 91–365 days and >365 days, respectively, following antibiotic receipt. Conclusions: Reduced risk of COVID-19 among PCV13 recipients, transiently attenuated by antibiotic exposure, suggests that pneumococci may interact with SARS-CoV-2. Abstract : After adjusting for risk factors and other exposures, adults aged ≥65 years who received 13-valent pneumococcal conjugate vaccine (PCV13) experienced lower incidence of COVID-19 diagnosis, hospitalization, and death. Antibiotic receipt transiently attenuated the association between PCV13 receipt and COVID-19 diagnosis.